1997
DOI: 10.1038/sj.bmt.1701015
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage cell composition in allogeneic bone marrow transplant patients without symptomatic lung complications

Abstract: Summary:that it is similar to that seen in healthy volunteers is not based on solid data. Only a few articles have included a small group of asymptomatic BMT patients as a comparaThe purpose of this study was to assess the cytological composition of bronchoalveolar lavage (BAL) fluid in tive or control group. [1][2][3][4][5][6] Observations in healthy individuals have contributed to define the inflammatory and immune allogeneic BMT patients without lung complications and compare it with that obtained from heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…These data agree with previous reports but it has to be taken into account that in a study by de la Camara et al 7 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These data agree with previous reports but it has to be taken into account that in a study by de la Camara et al 7 …”
Section: Discussionsupporting
confidence: 78%
“…[2][3][4][5] BAL cytology after BMT/PBSCT has not been studied extensively and information about the presence of pro-and antiinflammatory cytokines in this compartment is sparse. [6][7][8][9] Previous studies have investigated cytokine patterns in serum and peripheral blood cells after BMT/PBSCT in case of infection and GVHD. [10][11][12] GVHD is characterized by activation of Th1 subsets of CD4 + helper cells resulting in interleukin-2 production.…”
mentioning
confidence: 99%
“…It was shown to be useful in the assessment of chronic lung rejection after lung transplantation [9] but it has never been studied in patients undergoing HSCT. A previous study has shown that bronchoalveolar lavage neutrophil counts increased during the first 6 months after HSCT in patients without overt pulmonary complications [10]. Similarly, fraction of exhaled nitric oxide (FeNO), a non-invasive marker of airway inflammation, has been used to monitor lung transplantation rejection [11] but its utility has been poorly assessed after HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Its use as a research or surveillance tool must therefore be based on clear evidence of its safety. Most reports of BAL in transplant recipients without respiratory impairment imply acceptable safety without detailing complications, 5,7,[9][10][11][12][13] and where rates are quoted they are low (eg 2% 14 ). The subjects of these reports were not neutropenic.…”
mentioning
confidence: 99%